French Translation and Validation of Three Scales Evaluating Stigma in Mental Health - Garcia, Carla; Golay, Philippe; Favrod, Jérôme; Bonsack, Charles (Frontiers in Psychiatry, 2017)
Objective: The concept of stigma refers to problems of knowledge (ignorance), attitudes (prejudice) and behavior (discrimination). Stigma may hinder access to care, housing and work. In the context of implementation of programs such as “housing first” or “individual placement and support” in French speaking regions, validated instruments measuring stigma are necessary. “Attitudes to Mental Illness 2011” is a questionnaire that includes three scales measuring stigma through these three dimensions. This study aimed to translate, adapt and validate these three scales in French. Methods: The “Attitudes to Mental Illness 2011” questionnaire was translated into French and back-translated into English by an expert. Two hundred and sixty-eight nursing students completed the questionnaire. Content validity, face validity, internal validity and convergent validity were assessed. Long-term reliability was also estimated over a three-month period. Results: Experts and participants found that the questionnaire’s content validity and face validity were appropriate. The internal validities of the three scales were also considered adequate. Convergent validity indicated that the scales did indeed measure what they were supposed to. Long-term stability estimates were moderate; this pattern of results suggested that the construct targeted by the three scales is adequately measured but does not necessarily represent stable and enduring traits. Conclusions: Because of their good psychometric properties, these three scales can be used in French, either separately, to measure one specific dimension of stigma, or together, to assess stigma in its three dimensions. This would seem of paramount importance in evaluating campaigns against stigma since it allows measures to be adapted according to campaign goals and the target population.